Remote Results after Mitral Valve Replacement - Pukas, K. V. (Ukrainian Journal of Cardiovascular Surgery, 2019)
Aim of investigation is to research properties of patients at remote period after mitral valve replacement (MVR). At ana-lyzed group are included 634 patients with mitral valve diseases, which were treated by MVR in National Amosov Institute of cardiovascular diseases from 1st January 2005 to 1st January 2007. Average being of research was 7.3 ± 0.9 years. Following values of research at 10-year step: survival 69.4%, stability of good results – 57.3%, freedom from thromboembolic events – 79.7%, freedom from reoperations – 95.4%. Plasty of LA was performed in 57 (10.1%) patients. Maze procedure was oc-cured in 39 (6.9%) patients. Concomitant tricuspid malformation (TV annuloplasty) was observed in 135 (23.7%) patients. Concomitant CABG was observed in 93 (5.0%) patients. Previous heart surgery (mainly closed mitral commissurotomy) had 129 (21.4%) patients. Reoperations were occured: thromboses (panus, paraprost. fistula) of mitral prostheses (n = 5), endocarditis (n = 3). AV blockade (pacemaker) was occured in 9 (1.6%) patients. Best results of mitral valve replacement were observed in remote period in patients at II–III NYHA class with presence of sinus rhythm. Patients must be followed-up with tightly observation especially risk group–IV functional class, atrial fibrillation, concomitant tricuspid valve diseases, left atriomegaly (diameter of 6.0 cm or more), ejection fraction less than 0.45, high pulmonary hypertension (PASP > 70 mmHg), CABG + progressive ischemic heart disease, left ventriculomegaly (ESVI > 95 ml/mq), female, age more than 60 years. Mitral valve replacement with operation Maze allows successfully renew sinus rhythm on a hospital stage, and stabilize it well during half-year after operation.